The Main Characters’ Language Style Matching in To All the Boys I’ve Loved Before Movie - Tilana, Olivia (English Literature Study Program, 2023)
This research aimed to investigate the use of function words, verbal mimicry, and non-verbal language styles in assessing the alignment of language styles between individuals. The film